Weed Management in Moth bean (Vigna aconitifolia) in Arid Region of Rajasthan - Saxena, Anurag; Singh, Y V; Singh, D V; singh, Raj (Annals of Arid Zone, 2016)
Field experiments were conducted at the Central Arid Zone Research Institute, Jodhpur, during three consecutive kharif seasons (1998 to 2000) to find out economical and effective weed management practices in moth bean. The results revealed that one hand weeding at 30 days after sowing was very effective in reducing population and dry weight of weeds and also gave maximum weed control eniciency (72%). Application of lluchloralin at 0.75 and 1.00 kg ha-I was relatively more etTective in controlling weeds and increasing the seed yield of moth bean. The maxi’11um net returns were obtained with the application of lluchloralin at 0.75 kg ha-l ,but the maximum B:C ratio (1.23) was recorded with pre-plant incorporation of lluchloralin at 0.50 kg ha-’.